What are you hungry for? : the Chopra solution to permanent weight loss, well-being, and lightness of soul - Chopra, Deepak (Harmony Books, 2013)
"The New York Times bestselling author of Reinventing the Body, Resurrecting the Soul returns to his health and wellness roots with an exciting new approach to weight loss that focuses on the hungers we experience physically, mentally, and spiritually"--